Molecular Design of Non‐doped OLEDs Based on a Twisted Heptagonal Acceptor: A Delicate Balance between Rigidity and Rotatability. Issue 25 (11th February 2020) - Huang, Zhenmei; Bin, Zhengyang; Su, Rongchuan; Yang, Feng; Lan, Jingbo; You, Jingsong
Abstract: The development of efficient non‐doped organic light‐emitting diodes (OLEDs) is highly desired but very challenging because of a severe aggregation‐caused quenching effect. Herein, we present a heptagonal diimide acceptor (BPI), which can restrict excessive intramolecular rotation and inhibit close intermolecular π–π stacking due to well‐balanced rigidity and rotatability of heptagonal structure. The BPI‐based luminogen (DMAC‐BPI ) shows significant aggregation‐induced delayed florescence with an extremely high photoluminescence quantum yield (95.8 %) of the neat film, and the corresponding non‐doped OLEDs exhibit outstanding electroluminescence performance with maximum external quantum efficiency as high as 24.7 % and remarkably low efficiency roll‐off as low as 1.0 % at 1000 cd m −2, which represents the state‐of‐the‐art performance for non‐doped OLEDs. In addition, the synthetic route to DMAC‐BPI is greatly streamlined and simplified through oxidative Ar−H/Ar−H homo‐coupling reaction. Abstract : Power of twist : A twisted heptagonal diimide acceptor with well‐balanced structural rigidity and rotatability has been developed for the synthesis of a highly efficient aggregation‐induced delayed fluorescence material, which was used to make state‐of‐the‐art performance non‐doped OLEDs.